Guidance to applying for health research grants in the UK - Sathian, Brijesh; van Teijlingen, Edwin; Banerjee, Indrajit; Kabir, Russell (Nepal Journal of Epidemiology, 2022)
Applying for a research grant is one of the skills new researchers need to learn. Writing a grant application can be an intimidating process. Most research funders have either an online application system or a standard application form that can be emailed to the funder. Although the length and layout of a grant application can vary between funding bodies, most ask for similar details, including a research proposal, the nature of the research team, a budget, a timeline, and often a risk assessment. This paper summarises key funding agencies in the health research field. Furthermore, it briefly outlines the general process of applying for grants related to health and health services research in the UK. To highlight some of the issues that can occur in the grant application process, we provide two examples of applications for international research grants from UK-based funding bodies, each had to be resubmitted before of it was successful in receiving funding.